2008
DOI: 10.1158/1078-0432.ccr-07-2245
|View full text |Cite
|
Sign up to set email alerts
|

Capitalizing on the Immunogenicity of Dying Tumor Cells

Abstract: Cancer cell death occurs continually during tumor development and progression, whereas the selective killing of surviving cancer cells remains the primary objective of antineoplastic treatments. Recent insights into the immunologic consequences of cancer cell death have begun to elucidate the ways in which host antitumor immunity is shaped during cancer pathogenesis and then modulated by therapeutic intervention. Dying tumor cells evoke a range of host responses, dependent in part upon the mode of cell death, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Stress-induced cancer cell death by means of apoptosis, necrosis, and autophagy occurs continually during tumour development and progression (Fonseca and Dranoff, 2008). What the ramifications of this to the tumour microenvironment is only beginning to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced cancer cell death by means of apoptosis, necrosis, and autophagy occurs continually during tumour development and progression (Fonseca and Dranoff, 2008). What the ramifications of this to the tumour microenvironment is only beginning to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death confers immunogenic properties to tumor cells (45)(46)(47). In particular, necrotic cell death has long been regarded as immunogenic due to the release of damage-associated molecular patterns, like heat shock protein 70, high mobility group box 1 (48,49), and lipid membranes (50).…”
Section: Discussionmentioning
confidence: 99%
“…Its development including malignancy grade and patient prognosis is influenced not only by the mutations that suffer tumor cells, but also by the status of the immune system, which interacts with tumor microenvironment [1]. Some authors have reported that the immune system is unable to halt tumor progression and even more it is responsible of promoting tumorigenesis [2]. Innate immune cells, like dendritic cells (DC), natural killer cells, granulocytes, macrophages and monocytes are present in the normal mammary gland and play an important role participating in its development and remodeling, but they are also present in neoplastic tissues, such as breast tumors.…”
Section: Introductionmentioning
confidence: 99%